ANALISIS PENYEBAB ADDENDUM DAN PENGARUHNYA TERHADAP EFEKTIVITAS PEMBANGUNAN KAPAL WISATA TRIMARAN - Putri Marthasari; Fitri Hardiyanti; Irma Rustini Aju (Proceeding Maritime Business Management Conference, 2022)
In construction, punctuality is a very important thing. The problem that often occurs is a change in thecontract (contract addendum). The purpose of this study was to determine the determination of the S Curve before and after the contract addendum, analyze the causes of the occurrence, determine the effect on the effectiveness of the shipbuilding that occurred at PT. Dumas Tanjung Perak Shipyards, and see changes in time variants. This research uses quantitative methods which are carried out through interviews and questionnaires. From these results will be tested with validity test, reliability test, Multiple Linear Regression analysis test, Correlation analysis, Determination analysis, F test and T test. The results of the multiple linear regression test, namely environmental factors are the most dominant factors that affect the implementation time with regression coefficient of 2.350, financial and administrative factors affect the cost of implementation with a regression coefficient of 1.130. The correlation test concluded that there was a very strong relationship between the independent variable and the dependent variable. The results of the determination test concluded that effectiveness had an effect on implementation time of 93.7%, and effectiveness had an effect on implementation costs of 90.8%. There are 5 factors that cause the addendum contract and a change in the implementation time of this tourismship construction project by 23.6%.